The global, regional burden of pancreatic cancer and its attributable risk factors from 1990 to 2021 - Weidong Yu; Danyi Zhou; Fanhao Meng; Jinjing Wang; Bo Wang; Jianling Qiang; Lijun Shen; Maofeng Wang; Hezhi Fang (BMC Cancer)
Abstract Background Pancreatic cancer is the 12th most common type of cancer, and the sixth leading cause of cancer-related mortality, worldwide. Up-to-date statistics on pancreatic cancer would provide us with a better understanding of epidemiology and identify the causative risk factors for the prevention of this disease. Methods The degree and change patterns of exposure as well as the attributable cancer burden, including incidence, mortality, disability-adjusted life years (DALYs), and prevalence in global and regional, by sex, age, year, for pancreatic cancer, with the data extracted from the Global Burden of Diseases Study (GBD) 2021. All data analyses were conducted using linear regression analysis and the Joinpoint software (version 5.0.1). Results In 2021, 508,533 new cases of pancreatic cancer have been reported; the mortality and prevalence rate increased to 5.95, and 5.12 respectively; and the global DALYs rate increased to 130.33 this year. Besides, the pancreatic cancer-associated rates of incidence, mortality, DALYs, and prevalence were higher in males than in females. In addition, these indicators in the high SDI (Sociodemographic index) region were higher than the global mean. To date, the high fasting plasma glucose remained the major risk factor that influenced the incidence, mortality, DALYs, and prevalence of pancreatic cancer, followed by tobacco and high body mass index (BMI). Conclusions Results of this study suggest that the burden of pancreatic cancer is increasing generally, therefore, more attention and measures should be taken to cope with this situation.